Development Of First High School Mathematics LKPD Based On Case Method Integrated Local Culture Mandailing Tribe - Ningsih Sagala, Prihatin; Suhendro L, Pristi; Widyastuti, Eri (International Journal of Educational Research & Social Sciences, 2022)
Learning is a process of interaction between students and teachers, with lesson materials, delivery methods, learning strategies and learning resources in a learning environment. The success of learning can be seen through the level of success in achieving educational goals. Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed by themselves, society, nation and state, and have global mindset. The implementation of learning with the case method model is carried out to overcome the problems that arise as a result of the Limited Face-to-face Learning (PTMT) policy, such as less active student learning activities, low student learning responses and low student learning outcomes. Junior high school students belonging to the Generation Z category have an attitude of openness, this generation accepts various views and mindsets, causing them to easily accept diversity and differences in views. As a result, Gen Z becomes difficult to define themselves, selfidentity changes based on the factors that influence their thinking. Therefore, it is very important to restore national identity or introduce the cultural identity of the surrounding community so as not to be eroded by the development of the outside world which makes generation Z forget local culture, one of which is the Mandailing Tribe Culture in North Sumatra. The development research uses the ADDIE Model by integrating the Local Culture of the Mandailing Tribe in North Sumatra in developing the Mathematics LKPD for Grade VII Junior High Schools based on students' initial perceptions of the current condition of Generation Z. The use of the Case Method approach aims to improve students' critical thinking skills based on the cases presented in the teaching materials.